President Vs Congress in US Foreign Policy: Cooperation or Confrontation - Zahid Ali Khan & Munawar Sabir (Journal of Political Studies, 2024)
The powers to formulate foreign policy had been divided between the president and the Congress with an object to achieve continuity, coherence, and consistency in foreign policy. Both have opportunity to change features of foreign policy, to approach complete process and to execute and implementation of foreign policy. The formation of US foreign policy is more difficult and complex, and the support of these two branches is required for the making of strong and effective foreign policy. Check and balance is the key feature of relations between the President and Congress. This is the most important feature of the US political system in order to prevent the one organ of Government to become so powerful to impose its hegemony and the domination over the other. The dispersal of power over foreign policy puts a heavy premium on consultation, coordination, and cooperation by these two important organs of US Government.